Self-penile amputation and castration: A rare and life-threatening form of genital self-mutilation (Indian Journal of Case Reports, 2022)
Self-castration and penile amputation are rare life-threatening types of genital self-mutilation. The microsurgical technique of penile replantation is the gold standard; however, there are conflicting reports of successful macrosurgical penile replantations. Being rare, this condition may even be mistaken as criminal genital mutilation. The surgical management of penile amputation evolves over a few case reports and case series; therefore, it is prudent to publish such rare phenomena to make more awareness among the clinicians to initiate prompt and effective treatment. We report a case of self-multiple penile amputations and castration in a 70-year-old man suffering from bipolar disorder who also had failed macrosurgical penile replantation. To the best of our knowledge, this is the first case of self-multiple penile amputation with castration reported in the literature. Although ours is a single case experience, yet the macrosurgical replantation in multiple penile amputations is likely to be unsuccessful.